Comparison of the flexibility of standard Salesforce components and custom components in Lightning Web Components - Tomasz Olszewski; Klaudia Parczyńska; Marek Miłosz (Journal of Computer Sciences Institute, 2025)
In modern business environments, flexibility and adaptability in customer relationship management solutions are increasingly important. This study examines the flexibility of Salesforce’s standard components compared to custom-developed components in Lightning Web Components by assessing each type’s customization and adaptability to business-specific needs. The research sets forth three primary hypotheses: that custom components are more adaptable to unique business requirements, that custom components enhance user satisfaction through better interface adaptation, and that they provide improved responsiveness across various devices. The methodology involved A/B testing with two groups, each evaluating either standard or custom Salesforce components on desktop and mobile devices. The evaluation focused on four flexibility metrics: CSS customizability, responsiveness, parameter flexibility, and user acceptability. Data collection included code analysis, component behavior observations, and user surveys. Findings indicate a significant flexibility advantage for custom components across all measured characteristics, confirming the hypotheses. In conclusion, the research demonstrates that custom components offer substantial flexibility benefits over standard components, particularly in enhancing user satisfaction and adaptability. These results suggest custom components are valuable for enterprises requiring high adaptability in their Salesforce solutions.